Protein, amino acid and fatty acid profiles of two edible crabs of Lagos coast,Nigeria: Amino and fatty acid contents of Nigerian crabs (Journal of the Bangladesh Agricultural University, 2019)
Edible crabs constitute one of the major sources of nutritious food for human nutrition. The study was aimed to examine the protein, amino acid and fatty acid compositions of two edible crabs (Callinectes amnicola and Portunus validus) of Lagos coast, Nigeria. Samples were obtained from the water body, transported in crushed iced insulated containers and analyzed in the laboratory using standard methods. Crude protein varied from 55 - 68.92% (C. amnicola) and 51.9 - 67.51% (P. validus) on dry matter basis. Leucine (8.63 - 9.73g/100 g crude protein) and glutamic acid (12.71 - 16.19g/100 g crude protein) were the highest concentrated essential and non-essential amino acids, respectively. The coefficient of variation of the amino acid values indicated that C. amnicola has more variations, relative to its mean. The most concentrated saturated fatty acid was palmitic acid in the samples with significantly different (P